Multiple scattering measurements in the mice experiment - Carlisle, T; Cobb, J; Neuffer, D (2012)
The international Muon Ionization Cooling Experiment (MICE), under construction atRAL, will test a prototype cooling channel for a future Neutrino Factory or Muon Collider.The cooling channel aims to achieve, using liquid hydrogen absorbers, a 10% reduction intransverse emittance. The change in 4D emittance will be determined with an accuracy of 1%by measuring muons individually. Step IV of MICE will make the first preciseemittance-reduction measurements of the experiment. Simulation studies using G4MICE, basedon GEANT4, find a significant difference in multiple scattering in low Z materials,compared with the standard expression quoted by the Particle Data Group. Direct measurementof multiple scattering using the scintillating-fibre trackers is found to be possible, butrequires the measurement resolution to be unfolded from the data. Copyright © 2012 byIEEE.